Charismatic Leadership and Organizational Commitment Mediated by Job Satisfaction Among Pesantren - Ibrohim, Busthomi; Zumrah, Abdul Rahim; Al Hakim, Muhamad Arief; Islami, Azmi (At-Ta'dib, 2025)
Purpose - Charismatic leadership is often regarded as a central leadership model in Islamic boarding schools (pesantren), especially due to the strong influence of the kyai as both religious and institutional leaders. However, the sustainability of teachers' organizational commitment in such institutions remains a challenge. This study aims to examine the direct influence of charismatic leadership on organizational commitment, as well as the mediating role of job satisfaction in this relationship. Methods - This research employed a quantitative survey method involving 566 educators from Pesantren Darunnajah Indonesia. Data were collected using validated instruments measuring charismatic leadership, job satisfaction, and organizational commitment. The data were analyzed using multiple regression analysis and the Baron and Kenny mediation test, supported by SPSS software. Findings - indicate that charismatic leadership significantly influences both job satisfaction and organizational commitment. Additionally, job satisfaction is found to mediate the relationship between charismatic leadership and organizational commitment. The level of charismatic leadership, job satisfaction, and organizational commitment among respondents was generally high. Implications/limitations: The findings provide empirical support for leadership development programs in pesantren that emphasize charismatic attributes such as vision, empathy, and personal influence. Originality/value: This study contributes to highlights the strategic role of the kyai not only as a religious figure but also as a professional leader within organizational frameworks.